Effectiveness of an educational intervention about inhalation technique in healthcare professionals in primary care: a cluster randomized trial - Vázquez-González, Noemí; Leiva-Fernández, José; Cotta-Luque, Víctor M.; Leiva-Fernández, Francisca; Rius-Díaz, Francisca; Martos-Crespo, Francisco; Martín-Montañez, Elisa; Barnestein-Fonseca, Pilar (Frontiers in Pharmacology, 2023)
Background: Incorrect inhalation technique is an important issue with regard to chronic obstructive pulmonary disease (COPD) patients and healthcare professionals. Studies are required in which counseling is carried out beforehand with healthcare professionals so that they can properly educate their patients. The objective of the present trial is to assess the improvement in the performance of the inhalation technique (IT) in subjects with COPD and prescribed inhaled therapy, after the implementation of an educational intervention by their general practitioners.Methods: Cluster randomized clinical trial. 286 COPD patients receiving scheduled inhalation therapy from 27 general practices in seven Primary Care Centers. Teach-back educational intervention for professionals and patients. Primary outcome: performance of the correct inhalation technique. It is considered a good technique if all steps of the inhalation data sheet are correctly performed. Secondary outcomes: forced spirometry, Basal Dyspnea Index, Medical Research Council dyspnea scale, St George's Respiratory Questionnaire and EuroQoL5D-5L as health-related quality of life. One-year follow-up. Intention to treat analysis.